Možnosti za deregulacijo poklicev v gradbeništvu med konkurenčnostjo, kakovostjo in varnostjo - Zirnstein, Elizabeta (Gradbeni vestnik, 2012)
The regulation of professions, i.e. the establishment of formal conditions for the pursuit of a certain profession, is also typical for the construction industry sector. Since both, the European Union and Slovenia, undertook to eliminate administrative and other obstacles in order to increase the competitiveness of the economy, the issue of deregulating professions (again) became a topic of interest. For the construction industry, the deregulation of professions, i.e. the elimination of formal requirements for the pursuit of a certain profession, is a very sensitive issue, principally because inappropriate and imprudent deregulation might cause adverse effects in several areas. Based on the comparative legal analysis, presented in the paper, the deregulation of professions in civil engineering should be considered in the sense of a re-regulation or better regulation. This process requires appropriate cooperation from the expert public and should take into account all impacts that might be brought about by any case of deregulation, including those concerning the psychosocial area and tertiary education.
Keywords: civil engineering; deregulacija; gradbeništvo; poklici; regulacija